PENYUSUNAN MODUL PRAKTIKUM BERBASIS PENELITIAN - Ismarisa, Ahilam; Waris, Waris; Primiani, Cicilia Novi (UNIVERSITAS PGRI MADIUN, 2023)
The practical manual is a guide for experimental activities needed in laboratory learning, based on the concept of the scientific method. The current practicum manual is structured textually so that it does not direct students in formulating problems. The purpose of the study was to compile a practicum manual based on the results of the research. Descriptive research method, with procedures for compiling a practicum manual from the results of research that has been carried out. The structure of the practicum manual is in accordance with the practicum manual, accompanied by pictures of research results. Validation by two validators, namely material expert validator and learning media expert. The data collection technique was carried out using a feasibility questionnaire instrument for practicum guidelines. The analysis of the validation results was carried out descriptively. The results of the validation of the preparation of the practicum manual with a feasibility level of 79.1% on the aspect of material validity and 84.21% on the validity of the media with good criteria.